The Importance of Inclusive Education and Correlation with Self-Concept among Students: A Conceptual Literature Review - Julien, Gabriel (Journal of Educational Research and Practice, 2025)
Inclusive education is pivotal in promoting equitable learning opportunities and nurturing student self-development. This study systematically reviews relevant literature to explore the significance of inclusive education and its correlation with self-concept among students. Using a qualitative descriptive approach, this conceptual study draws on various peer-reviewed sources that address inclusive pedagogical practices, student identity formation, and psychosocial learning environments. The analysis reveals that inclusive education positively influences students' self-concept by fostering a sense of belonging, autonomy, and competence within the school setting. Teachers' attitudes, peer interactions, and institutional support are critical factors shaping students' self-perception in inclusive environments. Furthermore, inclusive classrooms promote mutual respect and reduce stigmatization, improving academic and socio-emotional outcomes. This paper also highlights challenges in implementation, such as limited teacher training and societal prejudice, which may hinder the development of a healthy self-concept among learners with diverse needs. The findings suggest that to optimize student self-concept, inclusive education must be approached holistically—integrating curriculum design, teacher preparedness, and school-wide inclusion policies. The study provides conceptual insights that may inform educational practitioners, policymakers, and researchers in designing inclusive strategies that support student identity and well-being. Limitations and directions for future empirical research are discussed.